The near‐global mesospheric potassium layer: Observations and modeling. Issue 15 (7th August 2015) - Dawkins, E. C. M.; Plane, J. M. C.; Chipperfield, M. P.; Feng, W.
Abstract The meteoric metal layers act as unique tracers of chemistry and dynamics in the upper atmosphere. Existing lidar studies from a few locations show that K exhibits a semiannual seasonality (winter and summer maxima), quite unlike the annual seasonality (winter maximum and summer minimum) seen with Na and Fe. This work uses spaceborne observations made with the Optical Spectrograph and InfraRed Imager System instrument on the Odin satellite to retrieve the near‐global K layer for the first time. The satellite data (2004 to mid‐2013) are used to validate the implementation of a recently proposed potassium chemistry scheme in a whole atmosphere chemistry climate model, which provides a chemical basis for this semiannual seasonal behavior. The satellite and model data show that this semiannual seasonality is near global in extent, with the strongest variation at middle and high latitudes. The column abundance, centroid layer height, and root‐mean‐square width of the K layer are consistent with the limited available lidar record. The K data set is then used to investigate the impact of polar mesospheric clouds on the metal layers at high latitudes during summer. Finally, the occurrence frequency of sporadic K layers and their possible link to sporadic E layers are examined.